Dataset of the effect of the number of injector holes on the heat transfer coefficient and the pressure in the combustion chamber of a hydrogen-diesel engine (2024)
There are several methods for simulating internal combustion engines. The computational fluid dynamics method is the best way to simulate these engines because it can simulate the combustion process, which is a microscopic process. In this study, the simulation of the combustion process in a closed cycle in a diesel engine with a mixture of diesel and hydrogen is done by AVL Fire software. In order to simulate the combustion in the Species and chemical transmission section, a chemkin mechanism is coupled with AVL Fire software. In this study, the effect of 10 % hydrogen fuel and 90 % diesel fuel as well as the effect of nozzle holes (1, 3 and 6 holes) on the engine performance were directly investigated. In order to validate the results of the pressure simulation and the temperature inside the cylinder in the diesel fuel combustion mode, at 2800 rpm and 100 % load, the data were compared with the experimental data. The research also included verification of the heat transfer coefficient (HTC) results with theoretical data obtained by Woschni and Hohenberg. To accurately simulate the combustion process, the simulation data was validated by comparing the pressure and temperature inside the cylinder at a specific operating condition with experimental data. The results indicate that the maximum heat transfer coefficient is achieved at the angle of maximum pressure, with the exhaust valve having the highest coefficient. The addition of hydrogen to diesel fuel results in a 1.72 % increase in the heat transfer coefficient due to increased collisions. In addition, the introduction of hydrogen fuel increases cylinder pressure and engine power, while increasing the number of fuel nozzle holes decreases the coefficient and pressure, which affects fuel penetration and evaporation rate.